Air pollutants and primary liver cancer mortality: a cohort study in crop-burning activities and forest fires area - Thongsak, Natthapat; Chitapanarux, Taned; Chotirosniramit, Anon; Chakrabandhu, Somvilai; Traisathit, Patrinee; Nakharutai, Nawapon; Srikummoon, Pimwarat; Thumronglaohapun, Salinee; Supasri, Titaporn; Hemwan, Phonpat; Chitapanarux, Imjai (Frontiers in Public Health, 2024)
Introduction Northern Thailand experiences high levels of air pollution in the dry season due to agricultural waste burning and forest fires. Some air pollutants can enter the bloodstream, and the liver has the role of detoxifying these along with other harmful substances. In this study, we assessed the effects of long-term exposure to air pollutants on liver cancer mortality in this area. Methods A cohort of 10,859 primary liver cancer patients diagnosed between 2003 and 2018 and followed up to the end of 2020 were included in the study. Extended time-varying covariates of the annually averaged pollutant concentrations updated each year were utilized. The associations between air pollutants and mortality risk were examined by using a Cox proportional hazard model. Results Metastatic cancer stage had the highest adjusted hazard ratio (aHR) of 3.57 (95% confidence interval (CI):3.23–3.95). Being male (aHR = 1.10; 95% CI: 1.04–1.15), over 60 years old (aHR = 1.16; 95% CI: 1.11–1.21), having a history of smoking (aHR = 1.16; 95%CI: 1.11–1.22), and being exposed to a time-updated local concentration of PM2.5 of 40 μg/m3 (aHR = 1.10; 95% CI: 1.05–1.15) increased the mortality risk. Conclusion We found that air pollution is one of several detrimental factors on the mortality risk of liver cancer.